Aqueous electrolyte capable of being used for high-rate tin metal negative electrode and tin-manganese battery

By adding high-valent metal salts and charged water-soluble polymers to the aqueous electrolyte, the problems of uneven deposition and high polarization of tin particles are solved, and water-based tin metal with high magnification, long cycle life and high efficiency ion transport are achieved. Battery.

CN119481358AActive Publication Date: 2025-02-18GUANGDONG UNIV OF TECH

Patent Information

Application Number
CN202411634981.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing water-based tin metal batteries have deteriorated rate performance due to the uneven deposition and high polarization of tin particles, making it difficult to meet the needs of high reversibility and high stability.

Method used

By adding high-valent metal salts and charged water-soluble polymers to the aqueous electrolyte, the repulsion force and interface electric field distribution of the electric double layer are adjusted to achieve uniform and dense tin deposition.

Benefits of technology

The rate performance, Coulomb efficiency and cycle life of the tin metal anode and tin manganese batteries are significantly improved, ensuring efficient ion transport and stable tin deposition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481358A_ABST
    Figure CN119481358A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrochemical batteries, and particularly relates to an aqueous electrolyte capable of being used for a high-rate tin metal negative electrode and a tin-manganese battery. The aqueous electrolyte comprises an acidic solvent, a tin salt and various high-valence metal salts / charged water-soluble polymers, and can also comprise a manganese salt. According to the method, high-valence metal salt / charged water-soluble polymer is added into the aqueous electrolyte, the repulsive force of double electric layers is adjusted by using introduced charged particles, and the distribution of an electric field and a concentration field at an interface is homogenized, so that efficient ion transmission and uniform and compact tin deposition behaviors are realized. Meanwhile, the charged particles can effectively inhibit related side reactions on the manganese positive electrode side, so that the tin metal negative electrode and the tin-manganese battery can have long cycle life and excellent rate capability at the same time. In addition, the water-based electrolyte is low in raw material price and small in dosage, the reaction process is simple and mild, and the water-based electrolyte has good application and development prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical batteries, and in particular relates to an aqueous electrolyte that can be used for high-rate tin metal negative electrodes and tin-manganese batteries. Background Art

[0002] With the continuous growth of population, the rapid reduction of natural resource reserves and the continuous advancement of global energy transformation, the use of clean energy to replace traditional fossil fuels has become a global consensus. However, the high degree of dispersion and instability of clean energy has seriously reduced the possibility of its large-scale practical application. Therefore, it is crucial to develop a large-scale energy storage system that can efficiently utilize clean energy.

[0003] Rechargeable secondary batteries are important energy storage systems that utilize clean energy and have broad application prospects. They can be roughly divided into three systems: battery systems using non-aqueous electrolytes, aqueous electrolytes, and solid / quasi-solid electrolytes. Compared with the other two systems, aqueous batteries using aqueous electrolytes have higher safety and good ion transmission capabilities because water is the main solvent, and are considered to be more promising devices for large-scale energy storage in the future. Considering the gas production problem caused by the decomposition of water itself, the tin metal negative electrode has a high hydrogen evolution potential and a suitable theoretical capacity (451.6 mAh g -1 ) and low Young's modulus (42GP) are widely used in aqueous batteries, especially in acidic environments. However, the tetragonal crystal structure of tin metal and the similar surface energy of each crystal face lead to the formation of large tin particles during the deposition process, and it is very easy to fall off from the substrate during the cycle and turn into "dead tin" with no reaction activity. This greatly reduces the reversibility and stability of tin metal, making it difficult to meet the high requirements of grid-level energy storage. In response to the complex problems faced by tin metal anodes, researchers have proposed various strategies to improve the reversibility of tin metal. For example, the team of Professor Xia Yongyao of Fudan University [Yu Z, Wang Q, Li Y, et al. Highly reversible tin redox chemistry for stable anode-free acidic protonbattery [J]. Joule, 2024, 8, 1063.] reported a composite electrolyte (3 mol / L sulfuric acid + 0.2 mol / L tin sulfate + 1g·L -1Gelatin), the electrolyte can reduce the exchange current density and increase the polarization of the battery, thereby achieving orderly tin deposition. The team of Professor Lu Xihong of Sun Yat-sen University [Xu D, Zhang H, Xie J, et al. Highly Reversible Tin Film Anode Guided via Interfacial Coordination Effect for High Energy Aqueous Acidic Batteries [J]. Advanced Materials, 2024, 36, 2408067.] reported an electrolyte additive with a long chain (4-trioctylphenol pentaethoxylate), which can adjust the solvent sheath structure of tin ions and increase the nucleation overpotential, thereby achieving small-sized tin particle deposition. The above research results show that it is a desirable and effective strategy to modify the electrolyte to reduce the size of tin particles and thus improve their reversibility.

[0004] However, most current electrolyte modification methods mainly rely on mixing organic solvents or adding organic molecules to improve the performance of tin anodes. Although the tin particle size is reduced, the battery polarization also increases, which limits the ion transport capacity and leads to a decrease in rate performance. In addition, the uneven tin ion distribution and messy tin deposition sites will also affect the overall performance of the battery. Therefore, in order to develop aqueous tin metal batteries with high reversibility, high rate and high stability to achieve large-scale energy storage, it is necessary to design an aqueous electrolyte that can both regulate the tin deposition behavior and ensure efficient ion transport capabilities. Summary of the invention

[0005] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides an aqueous electrolyte that can be used for high-rate tin metal negative electrodes and tin-manganese batteries, the electrolyte using metal salts with high-valent ions / charged water-soluble polymers as additives. Due to the charge of the additives, these charged particles can act as competitive ions to regulate the double-layer repulsion, thereby effectively accelerating ion transport. At the same time, these charged particles can also homogenize the electric field distribution and tin ion concentration distribution at the interface to achieve dense and uniform tin deposition. In addition, the charged particles can also effectively alleviate the related side reactions on the manganese positive electrode side to achieve high-rate and long-life tin-manganese batteries.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention provides an aqueous electrolyte that can be used for high-rate tin metal negative electrodes and tin-manganese batteries, wherein the aqueous electrolyte comprises an acidic solution, a tin salt and a high-valent metal salt, or comprises an acidic solution, a tin salt, a manganese salt and a high-valent metal salt; the high-valent metal salt comprises indium sulfate, gallium sulfate, aluminum sulfate, chromium sulfate, iron sulfate, lanthanum sulfate, cerium sulfate, titanium sulfate, cobalt sulfate, nickel sulfate, lead sulfate, cadmium sulfate, zinc sulfate, copper sulfate and magnesium sulfate.

[0008] Preferably, the aqueous electrolyte further comprises a charged water-soluble polymer, and the charged water-soluble polymer comprises polyamine, polyquaternary ammonium salt, polyacrylic acid copolymer, polycarboxylate ether, ionic polyacrylamide, and ionic polyurethane.

[0009] The present invention adds a high-valent metal salt / charged water-soluble polymer to an aqueous electrolyte, uses the introduced charged particles to adjust the double-layer repulsion, and homogenizes the electric field and concentration field distribution at the interface, thereby achieving efficient ion transport and uniform and dense tin deposition behavior. At the same time, these charged particles can also effectively inhibit the related side reactions on the manganese positive electrode side, so that the tin metal negative electrode and the tin-manganese battery can have a long cycle life and excellent rate performance. In addition, the raw materials involved in the aqueous electrolyte are low in price, small in amount, and the reaction process is simple and mild, and has good application and development prospects.

[0010] Preferably, the tin salt includes tin sulfate, tin chloride, tin bromide, tin iodide, tin fluoride, tin oxalate, tin fluorophosphate, tin pyrophosphate, tin trifluoromethanesulfonate, tin tetrafluoroborate, tin nitrate, tin acetate.

[0011] Preferably, the acidic solution comprises sulfuric acid, hydrochloric acid, nitric acid, bromic acid, iodic acid, hydrofluoric acid, oxalic acid, phosphoric acid, diphosphoric acid, trifluoromethanesulfonic acid, tetrafluoroboric acid, nitric acid, and acetic acid.

[0012] Preferably, the manganese salt includes manganese sulfate, manganese chloride, manganese nitrate, manganese bromide, manganese iodide, manganese tin fluoride, manganese oxalate, manganese phosphate, manganese hydrogen phosphate, manganese dihydrogen phosphate, manganese trifluoromethanesulfonate, manganese nitrate, and manganese acetate.

[0013] Preferably, the concentration range of the tin salt is 0.01mol / L-1mol / L; the acidic solution is a mixture of acid and water, and the concentration range is 0.1mol / L-3mol / L; the concentration range of the high-valent metal salt is 0.01mol / L-1mol / L.

[0014] More preferably, the volume of the charged water-soluble polymer accounts for 0.01%-1% of the total electrolyte volume.

[0015] The second aspect of the present invention provides the use of the aqueous electrolyte described in the first aspect in the preparation of an aqueous battery, wherein the aqueous battery includes a tin symmetric battery, a tin asymmetric battery or a tin-manganese battery.

[0016] Preferably, the tin symmetric battery or the tin asymmetric battery is assembled by coupling tin foil and metal foil.

[0017] Preferably, the tin-manganese battery is assembled by coupling tin foil and a positive electrode current collector.

[0018] More preferably, the thickness of the tin foil mainly ranges from 50 μm to 200 μm.

[0019] More preferably, main materials of the metal foil include tin foil, copper foil, titanium foil, and aluminum foil, preferably tin foil and copper foil.

[0020] More preferably, the main material of the positive electrode current collector includes carbon felt, carbon paper, graphite paper, stainless steel mesh, copper foil, aluminum foil, titanium mesh, preferably carbon felt.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The present invention adds metal salts of high-valent ions / charged water-soluble polymers to the aqueous electrolyte. When the additives are applied to tin metal negative electrodes and tin-manganese batteries, the unique charge properties of these additives can not only homogenize the distribution of electric field and concentration field at the interface, but also effectively regulate the repulsive force of the double electric layer. Therefore, this characteristic can enable the tin metal negative electrode and tin-manganese battery to achieve rapid, uniform and dense tin deposition behavior and obtain excellent rate performance (30mA·cm -2 ), ultra-high Coulombic efficiency (99.96%) and ultra-long cycle life (7187 hours).

[0023] (2) The tin salt involved in the aqueous electrolyte of the present invention is economical, the concentration / proportion of the additives used is low, the process required to configure the electrolyte is simple, the reaction conditions are mild, the reaction time is short, and it is easy to prepare and store in large quantities. At the same time, the aqueous electrolyte can be used not only on tin metal negative electrodes, but also on other metal negative electrodes (such as copper foil, magnesium foil, indium foil, titanium foil, nickel foil, chromium foil, aluminum foil, etc.), metal powders (such as tin powder, indium powder, copper powder, magnesium powder, tungsten powder, chromium powder, germanium powder, cadmium powder, etc.), positive and negative electrode materials (such as MXene, manganese oxide compounds, vanadium oxide compounds, halogen elements, halides, etc.), etc. It can also be applied and has good application and development prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is the Tafel plot of the tin metal negative electrode in Comparative Example 1 and Example 1.

[0025] Figure 2This is a scanning electron microscope image of the tin metal negative electrode in Comparative Example 1 after cycling.

[0026] Figure 3 This is a scanning electron microscope image of the tin metal negative electrode in Example 1 after cycling.

[0027] Figure 4 This is a rate cycling curve of the symmetrical battery prepared with tin metal negative electrode in Comparative Example 1.

[0028] Figure 5 This is a rate cycling curve of the symmetrical battery prepared with tin metal negative electrode in Example 1.

[0029] Figure 6 The asymmetric battery prepared with tin metal negative electrode in Comparative Example 1 and Example 1 was subjected to a current density of 10 mA·cm -2 , the deposition surface capacity is 1 mAh cm -2 The cycle performance diagram below.

[0030] Figure 7 The electrochemical performance diagram of the tin-manganese battery prepared with tin metal negative electrode in Comparative Example 1 and Example 1 at different currents.

[0031] Figure 8 The surface capacity-voltage curve of the tin-manganese battery prepared with tin metal negative electrode at different currents in Comparative Example 1.

[0032] Fig. 9 The surface capacity-voltage curves of the tin-manganese battery prepared with the tin metal negative electrode at different currents in Example 1 are shown.

[0033] Fig.10 The tin-manganese battery prepared with tin metal negative electrode in Comparative Example 1 and Example 1 was subjected to a current density of 30 mA·cm -2 Long cycle performance diagram when . DETAILED DESCRIPTION

[0034] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0035] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0036] Example 1

[0037] This embodiment provides a method for preparing an aqueous electrolyte that can be used for high-rate tin metal negative electrodes and tin-manganese batteries. The detailed steps of the method are as follows:

[0038] (1) Weigh 17.18 g of tin sulfate and place it in a beaker, add 400 mL of 2 mol / L sulfuric acid, and stir until it is evenly mixed to obtain a 0.2 mol / L tin sulfate electrolyte.

[0039] (2) Take 200 mL of the tin sulfate electrolyte of step (1), add 5.18 g of indium sulfate thereto, and stir evenly to obtain the aqueous electrolyte that can be used for a high-rate tin metal negative electrode of Example 1.

[0040] (3) Take 100 mL of the aqueous electrolyte of step (2), add 30.2 g of manganese sulfate thereto, and stir evenly to obtain the aqueous electrolyte of Example 1 that can be used for high-rate tin-manganese batteries.

[0041] The electrolyte in step (2) is placed together with two pieces of tin metal and a separator in a 2032 button battery for coupling, and the symmetrical battery of Example 1 can be obtained. The electrolyte in step (2) is placed together with a piece of tin metal, a piece of copper foil and a separator in a 2032 button battery for coupling, and the asymmetrical battery of Example 1 can be obtained. The electrolyte in step (3) is placed together with a piece of tin metal and a piece of carbon felt positive electrode current collector in an electrolytic cell for coupling, and the tin-manganese battery of Example 1 can be obtained.

[0042] Comparative Example 1

[0043] This comparative example provides a method for preparing a tin metal negative electrode and an aqueous electrolyte for a tin-manganese battery. The detailed steps of the method are as follows:

[0044] (1) Weigh 17.18 g of tin sulfate and place it in a beaker, add 400 mL of 2 mol / L sulfuric acid, and stir until the mixture is evenly mixed to obtain an aqueous electrolyte for the tin metal negative electrode of Comparative Example 1.

[0045] (2) Take 100 mL of the aqueous electrolyte of step (1), add 30.2 g of manganese sulfate thereto, and stir until the mixture is evenly stirred to obtain the aqueous electrolyte of the tin-manganese battery of Comparative Example 1.

[0046] The electrolyte in step (1) is placed together with two pieces of tin metal and a separator in a 2032 button battery for coupling, thereby obtaining the symmetrical battery of comparative example 1. The electrolyte in step (1) is placed together with a piece of tin metal, a piece of copper foil and a separator in a 2032 button battery for coupling, thereby obtaining the asymmetrical battery of comparative example 1. The electrolyte in step (2) is placed together with a piece of tin metal and a piece of carbon felt positive electrode current collector in an electrolytic cell for coupling, thereby obtaining the tin-manganese battery of comparative example 1.

[0047] Figure 1 The scanning speed of the tin metal negative electrode in the comparative example 1 and the embodiment 1 is 1 mV·s in the three-electrode system. -1 The Tafel curve at the time. Figure 1 It can be seen that the corrosion potential of Example 1 is significantly higher than that of Comparative Example 1, and its corresponding corrosion current is also lower. This shows that the tin metal negative electrode in Example 1 is less prone to corrosion, and even if corrosion occurs, its rate will be significantly slower than that of Comparative Example 1, proving that the tin metal negative electrode in Example 1 has excellent corrosion resistance.

[0048] Figure 2 and Figure 3 The scanning electron microscope images of the tin metal negative electrode in Comparative Example 1 and Example 1 after 100 cycles are shown. It can be observed that a large amount of "dead tin" with uneven distribution exists on the surface of the tin metal negative electrode in Comparative Example 1 after the cycle. In contrast, the surface of the tin metal negative electrode in Example 1 remains flat and dense after the cycle, proving that the deposition process of tin in Example 1 is more uniform.

[0049] Figure 4 and Figure 5 The figure are the rate cycle curves of the symmetrical batteries prepared in Comparative Example 1 and Example 1 respectively. Figure 4 As shown in Figure 1, when the tin metal negative electrode is cycled in Comparative Example 1, the polarization of the battery increases rapidly with the increase of current density and reaches 10 mA·cm -2 When the Figure 6 As can be seen from the figure, the tin metal anode can operate stably at each current density, up to 30 mA cm -2 More importantly, when the current drops back to 1 mA cm -2 When the tin metal in Example 1 can still perform the deposition / dissolution behavior of tin ions normally, while the battery short circuit phenomenon has occurred in Comparative Example 1. These situations show that the tin metal negative electrode in Example 1 has excellent ion transport ability, which can ensure that the tin ion concentration remains uniformly distributed at a large rate, thereby achieving highly stable deposition / stripping behavior.

[0050] Figure 6The asymmetric battery prepared in Comparative Example 1 and Example 1 was subjected to a current density of 10 mA·cm -2 , the deposition surface capacity is 1 mAh cm -2 Cycle performance diagram when Figure 6 It can be seen that the tin metal negative electrode in Comparative Example 1 experienced less than 600 high reversible cycles before the coulombic efficiency dropped rapidly to 60%, indicating that too much "dead tin" was produced during the deposition / stripping process of tin and quickly fell off the substrate, resulting in the inability to maintain a high reversible cycle. In Example 1, the tin metal negative electrode was able to achieve 10,000 high reversible cycles with an average coulombic efficiency of 99.96%. This shows that the tin metal negative electrode in Example 1 has extremely high tin deposition / stripping reversibility and excellent cycle stability.

[0051] Figure 7 The electrochemical performance diagram of the tin-manganese battery prepared in Comparative Example 1 and Example 1 at different current densities. Figure 7 As shown, with the continuous increase of current density, the coulombic efficiency of the tin metal negative electrode in comparative example 1 decreases rapidly, which indicates that the reversibility of the tin metal negative electrode at high rates is poor. In Example 1, the tin metal negative electrode can always maintain a high coulombic efficiency, which indicates that the "dead tin" and ion transport problems are significantly alleviated in Example 1, and the tin ion concentration distribution can be kept uniform for a long time, thereby effectively inhibiting the growth of irregular large tin dendrites.

[0052] Figure 8 and Fig. 9 The following are the capacity-voltage curves of the tin-manganese batteries prepared in Comparative Example 1 and Example 1 at different current densities. Figure 8 It can be observed that with the continuous increase of current density, the discharge platform of the tin-manganese battery in comparative example 1 rapidly decreases and eventually disappears, which not only means that the ion transport capacity of the tin metal negative electrode in comparative example 1 is poor, but also reflects that many side reactions occur on the positive electrode side, resulting in a rapid decline in surface capacity. In sharp contrast, the discharge platform of the tin-manganese battery in Example 1 is always obvious and stable ( Fig. 9 ), which shows that the tin-manganese battery in Example 1 has excellent rate performance and effectively suppresses the side reactions occurring on the positive electrode side.

[0053] Fig.10 The tin-manganese battery prepared in Comparative Example 1 and Example 1 was subjected to a current density of 30 mA·cm -2 Long cycle performance diagram. Fig.10 It can be clearly found that the tin-manganese battery in Example 1 has a -2 It can provide about 0.5 mAh cm at a high current density. -2The reversible surface capacity of the battery can be maintained for nearly 6000 reversible cycles. However, the tin-manganese battery in Comparative Example 1 not only fluctuates frequently during the cycle, but also fails quickly after less than 2700 cycles. This shows that the tin-manganese battery in Example 1 not only has an excellent cycle life, but also has extremely high tin deposition / stripping reversibility.

[0054] Example 2

[0055] This embodiment provides a method for preparing an aqueous electrolyte that can be used for high-rate tin metal negative electrodes and tin-manganese batteries. The main differences between this method and embodiment 1 are as follows:

[0056] In step (2), 10.36 g of indium sulfate is added to 200 mL of 0.2 mol / L tin sulfate electrolyte to obtain an aqueous electrolyte that can be used for a high-rate tin metal negative electrode.

[0057] The remaining steps and experimental parameters involved were the same as in Example 1.

[0058] Example 3

[0059] This embodiment provides a method for preparing an aqueous electrolyte that can be used for high-rate tin metal negative electrodes and tin-manganese batteries. The main differences between this method and embodiment 1 are as follows:

[0060] In step (2), 2.59 g of indium sulfate is added to 200 mL of 0.2 mol / L tin sulfate electrolyte to obtain an aqueous electrolyte that can be used for a high-rate tin metal negative electrode.

[0061] The remaining steps and experimental parameters involved were the same as in Example 1.

[0062] Example 4

[0063] This embodiment provides a method for preparing an aqueous electrolyte that can be used for high-rate tin metal negative electrodes and tin-manganese batteries. The main differences between this method and embodiment 1 are as follows:

[0064] In step (2), 3.42 g of aluminum sulfate is added to 200 mL of 0.2 mol / L tin sulfate electrolyte to obtain an aqueous electrolyte that can be used for high-rate tin metal negative electrodes.

[0065] The remaining steps and experimental parameters involved were the same as in Example 1.

[0066] Example 5

[0067] This embodiment provides a method for preparing an aqueous electrolyte that can be used for high-rate tin metal negative electrodes and tin-manganese batteries. The main differences between this method and embodiment 1 are as follows:

[0068] In step (2), 4.28 g of gallium sulfate is added to 200 mL of 0.2 mol / L tin sulfate electrolyte to obtain an aqueous electrolyte that can be used for a high-rate tin metal negative electrode.

[0069] The remaining steps and experimental parameters involved were the same as in Example 1.

[0070] Example 6

[0071] This embodiment provides a method for preparing an aqueous electrolyte that can be used for high-rate tin metal negative electrodes and tin-manganese batteries. The main differences between this method and embodiment 1 are as follows:

[0072] In step (2), 0.4 mL of polyamine is added to 199.6 mL of 0.2 mol / L tin sulfate electrolyte to obtain an aqueous electrolyte that can be used for high-rate tin metal negative electrodes.

[0073] The remaining steps and experimental parameters involved were the same as in Example 1.

[0074] Example 7

[0075] This embodiment provides a method for preparing an aqueous electrolyte that can be used for high-rate tin metal negative electrodes and tin-manganese batteries. The main differences between this method and embodiment 1 are as follows:

[0076] In step (2), 0.4 mL of polyamine and 2.59 g of indium sulfate are added to 199.6 mL of 0.2 mol / L tin sulfate electrolyte to obtain an aqueous electrolyte that can be used for a high-rate tin metal negative electrode.

[0077] The remaining steps and experimental parameters involved were the same as in Example 1.

[0078] Example 8

[0079] This embodiment provides a method for preparing an aqueous electrolyte that can be used for high-rate tin metal negative electrodes and tin-manganese batteries. The main differences between this method and embodiment 1 are as follows:

[0080] In step (2), 0.4 mL of polyamine and 3.42 g of aluminum sulfate are added to 199.6 mL of 0.2 mol / L tin sulfate electrolyte to obtain an aqueous electrolyte that can be used for high-rate tin metal negative electrodes.

[0081] The remaining steps and experimental parameters involved were the same as in Example 1.

[0082] Example 9

[0083] This embodiment provides a method for preparing an aqueous electrolyte that can be used for high-rate tin metal negative electrodes and tin-manganese batteries. The main differences between this method and embodiment 1 are as follows:

[0084] In step (2), 0.4 mL of polyamine and 4.28 g of gallium sulfate are added to 199.6 mL of 0.2 mol / L tin sulfate electrolyte to obtain an aqueous electrolyte that can be used for high-rate tin metal negative electrodes.

[0085] The remaining steps and experimental parameters involved were the same as in Example 1.

[0086] The symmetrical cells prepared in Examples 1-5 and Comparative Example 1 were heated to a current density of 1 mA·cm -2 , the deposition surface capacity is 1 mAh cm -2 The electrochemical test results are shown in Table 1.

[0087] It can be seen from Table 1 that the cycle life of Examples 1-5 all exceeds that of Comparative Example 1, among which Example 1 has the best electrochemical performance, indicating that the improvement effect of this example is the most obvious.

[0088] Table 1 Cycle life of symmetrical batteries in Examples 1-5 and Comparative Example 1

[0089] Cycle life (hours) Example 1 7187 Example 2 2500 Example 3 1521 Example 4 1388 Example 5 800 Comparative Example 367

[0090] The asymmetric cells prepared in Examples 3-9 and Comparative Example 1 were heated to a current density of 5 mA·cm -2 , the deposition surface capacity is 1 mAh cm -2 The electrochemical test results are shown in Table 2.

[0091] It can be seen from Table 2 that the first coulombic efficiency of Examples 3-9 is better than that of Comparative Example 1. After adding a trace amount of polyamine, the first coulombic efficiency is improved, but the polarization voltage is also slightly increased, which may reduce the ion transmission rate to a certain extent. After adding the high-valent metal salt and the polyamine at the same time, the first coulombic efficiency can be further improved and the polarization voltage can be reduced. This shows that there is a positive synergistic effect between the high-valent metal salt and the polyamine, so that while maintaining a highly reversible deposition behavior, good tin ion transmission kinetics can also be achieved.

[0092] Table 2 First coulombic efficiency and polarization voltage of asymmetric cells in Examples 3-9 and Comparative Example 1

[0093]

[0094]

[0095] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. An aqueous electrolyte that can be used for high-rate tin metal negative electrodes and tin-manganese batteries, characterized in that: The aqueous electrolyte includes an acidic solution, a tin salt and a high-valent metal salt, or includes an acidic solution, a tin salt, a manganese salt and a high-valent metal salt; the high-valent metal salt includes indium sulfate, gallium sulfate, aluminum sulfate, chromium sulfate, iron sulfate, lanthanum sulfate, cerium sulfate, titanium sulfate, cobalt sulfate, nickel sulfate, lead sulfate, cadmium sulfate, zinc sulfate, copper sulfate and magnesium sulfate.

2. The aqueous electrolyte for high-rate tin metal negative electrode and tin-manganese battery according to claim 1, characterized in that: The aqueous electrolyte also includes a charged water-soluble polymer, and the charged water-soluble polymer includes polyamine, polyquaternary ammonium salt, polyacrylic acid copolymer, polycarboxylate ether, ionic polyacrylamide, and ionic polyurethane.

3. The aqueous electrolyte for high-rate tin metal negative electrode and tin-manganese battery according to claim 1, characterized in that: The tin salts include tin sulfate, tin chloride, tin bromide, tin iodide, tin fluoride, tin oxalate, tin fluorophosphate, tin pyrophosphate, tin trifluoromethanesulfonate, tin tetrafluoroborate, tin nitrate, and tin acetate.

4. The aqueous electrolyte for high-rate tin metal negative electrode and tin-manganese battery according to claim 1, characterized in that: The acidic solution includes sulfuric acid, hydrochloric acid, nitric acid, bromic acid, iodic acid, hydrofluoric acid, oxalic acid, phosphoric acid, diphosphoric acid, trifluoromethanesulfonic acid, tetrafluoroboric acid, nitric acid, and acetic acid.

5. The aqueous electrolyte for high-rate tin metal negative electrode and tin-manganese battery according to claim 1, characterized in that: The manganese salts include manganese sulfate, manganese chloride, manganese nitrate, manganese bromide, manganese iodide, manganese tin fluoride, manganese oxalate, manganese phosphate, manganese hydrogen phosphate, manganese dihydrogen phosphate, manganese trifluoromethanesulfonate, manganese nitrate, and manganese acetate.

6. The aqueous electrolyte for high-rate tin metal negative electrode and tin-manganese battery according to claim 1, characterized in that: The concentration range of the tin salt is 0.01mol / L-1mol / L; the acidic solution is a mixture of acid and water, and the concentration range is 0.1mol / L-3mol / L; the concentration range of the high-valent metal salt is 0.01mol / L-1mol / L.

7. The aqueous electrolyte for high-rate tin metal negative electrode and tin-manganese battery according to claim 2, characterized in that: The volume of the charged water-soluble polymer accounts for 0.01%-1% of the total electrolyte volume.

8. Use of the aqueous electrolyte according to any one of claims 1 to 7 in the preparation of an aqueous battery, characterized in that: The aqueous battery includes a tin symmetric battery, a tin asymmetric battery or a tin-manganese battery.

9. The use according to claim 8, characterized in that: The tin symmetric battery or the tin asymmetric battery is assembled by coupling tin foil and metal foil.

10. The use according to claim 8, characterized in that: The tin-manganese battery is assembled by coupling tin foil and a positive electrode current collector.

Citation Information

Patent Citations

  • Aqueous electrolyte solution, and aqueous lithium ion secondary battery

    CN110021788A

  • Aqueous electrolyte and battery

    CN115312882A

  • Electrolyte for manganese-tin secondary battery

    CN116826129A

  • Aqueous stannous ion electrolyte capable of inhibiting dead tin and application of aqueous stannous ion electrolyte in tin-manganese battery

    CN118431590A

  • Process for filling micro-blind vias

    CN1799294A

Cited By

  • Water-based crown ether electrolyte capable of chelating stannous ions as well as preparation and application of water-based crown ether electrolyte

    CN120810014A

  • Water system rechargeable tin chloride secondary battery with high working platform

    CN121460742A